FMCG Sector Response to Covid-19: Impact on Supply Chain and Logistics - Sharma, Anup; Sharma, Anmol; Varun; Andrews, Dhanya; Roby, Rosmin (International Journal of Scientific Research and Management (IJSRM), 2021)
Covid-19 pandemic affected multiple disciplines. Almost all industries suffered owing to economic stress and Government regulations. Handling and transportation of goods became more challenging. FMCG sector was significantly affected by the pandemic and organizations adopted multiple strategies to keep themselves afloat. Multiple trade-offs were considered by organizations including partial closure, limited operational hours, and restructuring of the supply chain. Multiple reports across different industries were studied and supplemented with indepth interviews from the industry experts. The study revealed the use of innovative ways to reach customers. Organizations tried adopting lean practices in-order to support stressed-out logistics handlers